2010
DOI: 10.1103/physrevlett.104.216102
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of an Azobenzene Derivative on a Thin Insulating Layer by Inelastically Tunneling Electrons

Abstract: Scanning tunneling microscopy is used to investigate isomerization of amino-nitro-azobenzene on a thin NaCl layer on Ag(111) by inelastically tunneling electrons. A reversible isomerization between a planar trans and a three-dimensional cis form with two different thresholds is demonstrated. The isomerization characteristics are rationalized in terms of binding of the multipolar molecule to the ionic layer. This study shows the feasibility of a bistable single molecule switch on an insulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 26 publications
2
58
0
Order By: Relevance
“…In addition, scanning tunnelling microscopy (STM) has also been utilized to study surface chemical reactions by exploiting its ability to probe changes in electronic structure and large geometric changes of species reacting at a surface. [15][16][17][18][19] These techniques have played key roles in the development of surface chemistry and catalysis research. In addition to the structural changes in surface chemical reactions, electronic structures near the reaction sites also change significantly, so electronic spectroscopic techniques such as ultraviolet photoelectron spectroscopy (UPS) and X-ray photoelectron photoemission (XPS) have been widely used in experimental studies of surface chemistry and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, scanning tunnelling microscopy (STM) has also been utilized to study surface chemical reactions by exploiting its ability to probe changes in electronic structure and large geometric changes of species reacting at a surface. [15][16][17][18][19] These techniques have played key roles in the development of surface chemistry and catalysis research. In addition to the structural changes in surface chemical reactions, electronic structures near the reaction sites also change significantly, so electronic spectroscopic techniques such as ultraviolet photoelectron spectroscopy (UPS) and X-ray photoelectron photoemission (XPS) have been widely used in experimental studies of surface chemistry and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…The d level splitting diagram of a transition metal ion in a tetrahedral and a square-planar ligand field shown in figure 9, is a standard textbook example [32,33] . Since for a neutral copper atom the d-shell is completely filled with 10 electrons ([Ar]3d 10 4s 1 ), the electronic configuration of the metallic ion in the Cu(II) complex is [Ar]3d 9 . It is then immediately clear from the diagrams of figure 9 that the square-planar symmetry should be favored relative to the tetrahedral one, mainly because of the large energy gain due to the presence of an electron hole in the very energetically unfavorable dx2-y2 orbital.…”
Section: A Model Based On Crystal Field Theorymentioning
confidence: 99%
“…In fact, the structure is then governed by inter-ligands steric and electrostatic effects, which are not taken into account in CFT, and a tetrahedral geometry is adopted to minimize the repulsive interaction between the ligands. 9 ) should remain in the SP conformation because of the stabilizing effect of one or two holes in the dx2-y2 orbital. Then, it can be concluded that charging the Ni complex would not induce a change in the ligand symmetry.…”
Section: A Model Based On Crystal Field Theorymentioning
confidence: 99%
See 2 more Smart Citations